2006
DOI: 10.1021/bi052629q
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of All Cysteines in Tachyplesin I Abolishes Hemolytic Activity and Retains Antimicrobial Activity and Lipopolysaccharide Selective Binding

Abstract: Tachyplesin I is a cyclic beta-sheet antimicrobial peptide isolated from the hemocytes of Tachypleus tridentatus. The four cysteine residues in tachyplesin I play a structural role in imparting amphipathicity to the peptide which has been shown to be essential for its activity. We investigated the role of amphipathicity using an analogue of tachyplesin I (TP-I), CDT (KWFRVYRGIYRRR-NH(2)), in which all four cysteines were deleted. Like TP-I, CDT shows antimicrobial activity and disrupts Escherichia coli outer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 67 publications
6
105
0
Order By: Relevance
“…Current study identifies critical structural features of Pa4 for LPS recognition and provides a plausible mechanism of the outer membrane disruption. We believe that the LPS-bound structure of Pa4 and other finding in this study will be useful in the development of new antimicrobials with enhanced binding affinity for LPS (62,75).…”
Section: Nmr Structure Of Pardaxin In Lpsmentioning
confidence: 80%
“…Current study identifies critical structural features of Pa4 for LPS recognition and provides a plausible mechanism of the outer membrane disruption. We believe that the LPS-bound structure of Pa4 and other finding in this study will be useful in the development of new antimicrobials with enhanced binding affinity for LPS (62,75).…”
Section: Nmr Structure Of Pardaxin In Lpsmentioning
confidence: 80%
“…The impact of such a challenging problem has motivated numerous academic and pharmaceutical industry research groups to develop new drugs capable of dealing with the adaptation strategy (namely the selection of organisms adapted to some specific medium) that these organisms develop over time (Prates and Bloch Júnior, 2000;Fazio et al, 2006;Ramamoorthy et al, 2006;Che et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our proposition is based on the study carried out with tachyplesin-I mutants, in which the four existing cysteines of the natural peptide were replaced by tyrosine residues (Rao, 1999;Ramamoorthy et al, 2006). In the study with tachyplesin-I, the authors found a great similarity between the native and the mutant conformations.…”
Section: Introductionmentioning
confidence: 99%
“…For the lipid-binding experiment, different lipid concentrations of PC/PG SUVs (0, 85, 340, 680 and 1360 lM) or of PC SUVs (0, 83, 470, 748 and 1346 lM) were incubated with a fixed peptide concentration of 5 lM for 30 min as described previously [54]. Trp emission spectra were recorded using a 1-cm path length quartz cuvette on a spectrofluorometer (Jobin Yvon FluoroMax 3) with the excitation set at 280 nm using a slit width of 5 nm for both excitation and emission.…”
Section: Lipid-binding Experimentsmentioning
confidence: 99%